Republic of Estonia : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Macroeconomic performance and buffers were strong when the COVID-19 pandemic hit. Economic and social restrictions instituted in March 2020 helped slow new infections and mitigate negative health outcomes but triggered a deep decline in activity in Q2:2020. The slump was followed by a strong rebound in Q3 as the restrictions were eased. With the resurgence of the virus, pressures on the health system peaked in late-March 2021 and eased after a new round of restrictions. Going forward, the outlook is for a near-term economic recovery subject to large two-way risks. The strength and durability of the recovery hinges on the evolution of the health situation and the extent of economic scarring from the pandemic.